Green vibrational spectroscopic approach for simultaneous quantification of antihypertensive drugs in bulk and tablet formulations - Naga Prashant K; Suvarna Yenduri (Scientific Reports)
Abstract The selection of IR spectroscopic approach for quantification of drugs supports green analytical chemistry principles without compromising the method analytical performance. The method follows pressed pellet technique for preparing samples using potassium bromide without using any toxic solvents and even reduced waste too. An easy, fast, and environmentally friendly FT-IR spectrophotometric method was developed and validated for the simultaneous measurement of amlodipine besylate (AML) and telmisartan (TEL) in pharmaceutical combination formulations. The absorbance spectra which was obtained from obtained transmittance spectra were used for determining area under curve and correlated with amount or concentration. AML and TEL shows peaks at 1206 cm− 1 and 863 cm− 1. Validation of the developed method followed ICH guidelines and all the validation results were within the limits. The LOD and LOQ of AML were found as 0.009359 %w/w, 0.028359 %w/w respectively where for TEL it was found to be 0.008241 %w/w and 0.024974 %w/w respectively. The MoGAPI, AGREE prep, and RGB model assessment procedure was green and sustainable. The described HPLC technique was not significantly different statistically.